Downregulation of Interleukin-13 Receptor α2 Inhibits Angiogenic Formation Mediated by Chitinase 3-Like 1 in Late Atherosclerotic Lesions of apoE−/− Mice - Xue, Qi; Chen, Lei; Yu, Jianwu; Sun, Kewang; Ye, Lifang; Zheng, Jianlei (Frontiers in Physiology, 2021)
Aim: Chitinase 3-like 1 (CHI3L1) has the potential to prompt proliferation and angiogenic formation. Interleukin-13 receptor α2 (IL-13Rα2) was regarded as a receptor of CHI3L1, however, it is unknown whether CHI3L1 adjusts the neovascularization in late atherosclerotic lesions of apoE-/- mice via IL-13Rα2. Methods：Silicone collars were placed around one of the common carotid arteries of apoE-/- mice fed a high-fat diet. The mice were further injected with Ad. CHI3L1 alone or Ad.CHI3L1+Ad.IL-13Rα2 shRNA through caudal vein. The plaque areas in the whole aorta and aortic root were evaluated by Oil Red O staining and Hematoxylin/Eosin (H&E) staining. The contents of CD31, CD42b and collagen in carotid plaques were investigated by immunohistochemistry and masson trichrome staining. The role of CHI3L1 in migration and tube formation of HUVECs was determined by transwell and matrigel test. The effect of CHI3L1 on the expression of AKT and extracellular signal-regulated kinase (ERK) was evaluated with western blot. Results: The plaque loads in aorta were significantly more extensive in apoE-/- mice injected with Ad.CHI3L1 than those with Ad.CHI3L1+Ad.IL-13Rα2 shRNA. CHI3L1 significantly increased the contents of CD31 and CD42b and decreased the element of collagen in late-stage atherosclerotic lesions of the carotid arteries. The effects of CHI3L1 on migration, tube formation and upregulation of phospho-AKT and phospho-ERK of HUVECs were prohibited by inhibitors of phosphatidylinositol 3-kinase (PI3K) and Mitogen-activated protein kinase (MEK) as well as IL-13Rα2 shRNA. Conclusion: To some extent, CHI3L1 promotes migration and tube formation of HUVECs and neovascularization in atherosclerotic plaques possibly mediated by IL-13Rα2 through AKT and ERK signal pathways.